2001
DOI: 10.1159/000046829
|View full text |Cite
|
Sign up to set email alerts
|

How Plastic Is Spatial Hearing?

Abstract: The location of a sound source is derived by the auditory system from spatial cues present in the signals at the two ears. These cues include interaural timing and level differences, as well as monaural spectral cues generated by the external ear. The values of these cues vary with individual differences in the shape and dimensions of the head and external ears. We have examined the neurophysiological consequences of these intersubject variations by recording the responses of neurons in ferret primary auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…Convergence of visual and auditory inputs was also demonstrated in the brachium of the ferret IC (Doubell et al, 2000). The presence of different non-acoustic feedback signals in the IC could thus render it as a potential candidate for sound-localization plasticity also in mammals (King et al, 2001;King, 2002).…”
Section: Potential Mechanismsmentioning
confidence: 89%
“…Convergence of visual and auditory inputs was also demonstrated in the brachium of the ferret IC (Doubell et al, 2000). The presence of different non-acoustic feedback signals in the IC could thus render it as a potential candidate for sound-localization plasticity also in mammals (King et al, 2001;King, 2002).…”
Section: Potential Mechanismsmentioning
confidence: 89%
“…As these delays are highly reproducible from one device to the next (of the same make and model with the same features selected), they should not distort interaural time difference cues. Previous research has demonstrated the ability of listeners to adapt to small consistent differences in interaural time and level differences (Javer and Schwarz, 1995;King et al, 2001). As with all hearing aids, there is the likelihood of distortion of interaural time-and level-difference cues in the frequency region, typically in the range 250-500 Hz (but depending on degree of loss and size of the vent), where amplified sound and sound leaking in past the earmold or through the vent have similar magnitude (Dillon, 2001).…”
Section: A Effect Of Age Hearing Status Location and Test Materiamentioning
confidence: 99%
“…Plasticity in the spatial properties of the auditory SC maps has been demonstrated during adulthood and facilitated by behaviors that require spatial hearing, for ferret (King et al, 2001) and barn owl (Bergan, Ro, Ro, & Knudsen, 2005). Thus a computational theory of sound localization should include mechanisms that can re-calibrate after changes in sensory experience.…”
Section: Role Of Sensorimotor Experience In Auditory Spatial Perceptionmentioning
confidence: 99%